2019
DOI: 10.1177/1538192719830082
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Baccalaureate: Factors Shaping Latina/o Graduate Degree Aspirations

Abstract: This study examined how Latina/o undergraduate students' graduate and professional degree aspirations change during college. Using longitudinal data from the Cooperative Institutional Research Program, a multinomial logistic regression analysis was conducted to examine factors associated with aspiring to earn a degree beyond a baccalaureate. Findings show that many students change their initial aspirations and several college experiences, such as higher college GPA and faculty interactions, are associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In HD, linguistic capital was enacted by participants communicating their feelings and experiences and building relationships through shared stories, laughter, and tears during class sessions (Salinas, 2017). Framed in this positive manner, linguistic capital became a way to resist messages devaluing Latino identity and to increase resilience in the face of marginalization (Cuellar, 2024). Bilingual college students represented resistance to opposing messages regarding families’ native language.…”
Section: Discussionmentioning
confidence: 99%
“…In HD, linguistic capital was enacted by participants communicating their feelings and experiences and building relationships through shared stories, laughter, and tears during class sessions (Salinas, 2017). Framed in this positive manner, linguistic capital became a way to resist messages devaluing Latino identity and to increase resilience in the face of marginalization (Cuellar, 2024). Bilingual college students represented resistance to opposing messages regarding families’ native language.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Bradberry and De Maio (2019) suggested that degree aspirations were associated with undergraduate students' participation in experiential learning programs such as Model United Nationals and Judicial Internship programs. In addition, research using longitudinal data from the Cooperative Institutional Research program has shown that undergraduate students' graduate degree aspirations may change over time, since a higher GPA and levels of interactions with faculty can be associated with Latina/o students' graduate and professional degree aspirations (Cuellar & Gonzalez, 2021). As researchers, we acknowledge that there are disciplines that do not require a baccalaureate for employment and those which do not require a degree beyond a baccalaureate.…”
Section: Degree Aspirationsmentioning
confidence: 90%
“…GPA is widely used as a measure of success during and after completion of a bachelor's degree. Degree aspirations connect to student success because they suggest motivation to pursue higher level careers requiring graduate and professional school training (Cuellar & Gonzalez, 2021). The following subsections detail previous research on each of these components of student success.…”
Section: Student Successmentioning
confidence: 99%
“…Commonplace representations of the disciplineincluding how scientists and engineers are depicted in popular media, whom students see as their instructors and classmates, whose pictures hang in the hallways of their buildings, and who is depicted in course materials, etc.communicate to such students that they do not belong. This makes social and role identities a key consideration. , Institutional and programmatic policies may offer superficial support for cultural diversity and inclusion , but fail to make changes that align to these displayed values. Analysis of academic performance and persistence data in lower division chemistry courses reveals the differential impacts minoritized students experience: they are less likely to persist if they receive a lower grade and more likely to persist, compared to their privileged peers, if they receive a higher grade .…”
Section: Introductionmentioning
confidence: 99%